MYC‐associated and double‐hit lymphomas: A review of pathobiology, prognosis, and therapeutic approaches - Adam M. Petrich; Chadi Nabhan; Sonali M. Smith (2014)
Aberrant expression of the v‐myc avian myelocytomatosis viral oncogene homolog (MYC) proto‐oncogene has known transformative potential in healthy human cells. Chromosomal MYC rearrangements and consequent MYC overexpression is the defining lesion in Burkitt lymphoma (BL), conferring a highly proliferative state. However, abnormalities of MYC are increasingly appreciated in non‐BL histologies, including diffuse large B‐cell lymphoma (DLBCL) and B‐cell lymphomas intermediate between BL and DLBCL, with a particularly aggressive clinical phenotype. Although there are conflicting data regarding prognostic implications of isolated MYC aberrancy in these non‐BLs, the co‐occurrence of MYC rearrangements and either the antiapoptotic gene B‐cell chronic lymphocytic leukemia/lymphoma 2 ( BCL2 ) or the transcriptional repressor BCL6 leads to an entity termed double‐hit B‐cell lymphoma (DHL) (or triple‐hit if all 3 abnormalities are observed) with a particularly poor prognosis and no established treatment paradigms. Notably, a distinct pattern of gene expression profiling has been noted when MYC is overexpressed in BL compared with other lymphomas, supporting the notion that, although MYC promotes target gene transcription, the target genes vary by disease subtype. The frequency of MYC activity depends on the method of detection and ranges from 5% to 10% using fluorescence in situ hybridization but up to 30% of DLBCL using immunohistochemistry. Standard therapies developed for DLBCL are less effective when the disease is driven by MYC , leading to lower response rates and response durations. An important clinical challenge is to pre‐emptively identify MYC‐associated lymphomas and to subsequently develop trials specifically for this group of patients. However, the design of such studies is complicated by variable definitions of MYC ‐associated lymphoid malignancies and the lack of effective therapies to date. The objective if the current review was to evaluate the implications of MYC aberrancy with respect to the B‐cell lymphoma double‐hit and triple‐hit phenotypes and to consider the available data for clinical and practical management. Cancer 2014;120:3884–3895. © 2014 American Cancer Society .